2014
DOI: 10.1194/jlr.m044990
|View full text |Cite
|
Sign up to set email alerts
|

Spatial organization of lipids in the human retina and optic nerve by MALDI imaging mass spectrometry

Abstract: This article is available online at http://www.jlr.org signals to the visual centers of the brain ( 1 ). The central region is made up of several layers that include the horizontal, bipolar, and amacrine cells, which collectively process visual information from the photoreceptors, transmitting these signals to the ganglion cells. The outermost retinal neurons, the photoreceptors, are responsible for phototransduction ( 2 ). There are two types of photoreceptors, which include rods that are present in the perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 56 publications
2
58
0
Order By: Relevance
“…Hopefully, future developments in lipidomics such as secondary ion mass spectrometry (SIMS-C 60 ), which allows for profiling of lipids at the single-cell level 71 , may provide a useful platform to eventually solve the current debate over the presence of and biological relevancies of specific eicosanoids in specific cells during infection and inflammation. Recent studies on the spatial organization of lipids in the human retina and optic nerve by matrix-assisted laser desorption/ionization (MALDI) imaging mass spectrometry 72 identified individual phospholipids, some containing DHA, in different layers of the human retina, suggesting that with future technological advances local pools of released fatty acids and eicosanoid products may be detectable in relevant human tissues under inflammatory conditions.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…Hopefully, future developments in lipidomics such as secondary ion mass spectrometry (SIMS-C 60 ), which allows for profiling of lipids at the single-cell level 71 , may provide a useful platform to eventually solve the current debate over the presence of and biological relevancies of specific eicosanoids in specific cells during infection and inflammation. Recent studies on the spatial organization of lipids in the human retina and optic nerve by matrix-assisted laser desorption/ionization (MALDI) imaging mass spectrometry 72 identified individual phospholipids, some containing DHA, in different layers of the human retina, suggesting that with future technological advances local pools of released fatty acids and eicosanoid products may be detectable in relevant human tissues under inflammatory conditions.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…This molecular imaging technique has been applied to the investigation of lipids, metabolites and proteins in a plethora of pathophysiological processes(Carter et al 2011, Palmer et al 2012, Steven and Bunch 2013, Berry et al 2014, Djidja et al 2014, Jackson et al 2014, Jones et al 2014, Manier et al 2014, Seeley et al 2014, Shariatgorji et al 2014). By applying mass spectrometry to region-specific anatomical tissue architecture, MALDI-MSI offers another dimension in characterizing the natural history and development of these pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…There is currently limited information on the spatial distribution of biologically active small molecules in the lung in a physiological state(Sparvero et al 2012, Berry et al 2014) and in the numerous pathologies that present following radiation insult, and the devastating pneumonitis and fibrosis that develop. Work presented in this study documents lipidomic distribution and dysregulation in the lung following whole-thorax lung irradiation, as well as the detection and localization of AEOL 10150 within the lung tissue following irradiation and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The method is particularly well-suited for examining tissues of the eye as demonstrated by published images of lens [1218], retina [1924], and optic nerve [21, 25] tissues. In recent reports, distinct cell layers of the retina have been distinguished by IMS where unique lipid and metabolite signatures appear for each retinal layer [19, 21]. In optic nerve imaging studies, distinct lipid signatures have been reported for nerve fiber layers and surrounding dura mater in images acquired from rodent optic nerve tissue [25].…”
Section: Introductionmentioning
confidence: 99%